Hubungan Tipe Kepribadian Introvert dan Ekstrovert terhadap Risiko Perilaku Perundungan pada Pelajar di SMK Negeri 5 Jember - Geldine Raudina Freshta Delendra; Erti Ikhtiarini Dewi; Fitrio Deviantony (Pustaka Kesehatan, 2023)
Bullying behavior in adolescents is still found in the school environment. Introverted and Extroverted personality types can shape teenagers' behavior to risk bullying and shape their personality when they make friends or socialize. Bullying behavior causes bullies to experience problems in social interaction and a lack of empathy intensity. This study aims to analyze the relationship between Introverted and Extroverted personality types on the risk of bullying behavior in adolescents at SMK Negeri 5 Jember. This research method used analytic observational with a cross-sectional approach. Respondents in this study were 147 students of SMK Negeri 5 Jember and used the Stratified Random Sampling technique. The research was conducted online. Chi-Square test bivariate analysis (p<0.05). Introverted and Extroverted Personality Types Questionnaire and the Bullying Behavior Risk Questionnaire. The result was that 75 students (51%) were Extroverted personality types and had high risks of bullying. Adolescents with an extroverted personality type are more at risk of bullying because they easily socialize with peers and the surrounding environment and are more able to express themselves, so they often think bullying is just a joke. This study shows a value of 0.26 (p <0.05), which means there is a relationship between Introverted and Extroverted Personality Types on the Risk of Bullying Behavior.